MRI of the Prostate: Recommendations on Patient Preparation and Scanning Protocol - Franiel, Tobias; Quentin, Michael; Mueller-Lisse, Ullrich Gerd; Schimmoeller, Lars; Asbach, Patrick; Rödel, Stefan; Willinek, Winfried; Hueper, Katja; Beyersdorff, Dirk; Röthke, Matthias (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
The Working Group Uroradiology and Urogenital Diagnosis of the German Roentgen Society has developed uniform recommendations for the preparation and implementation of prostate MRI. In the first part detailed recommendations are given in tabular form regarding 1. anamnestic data before prostate MRI, 2. termination of examinations and preparation of examinations, 3. examination protocol and 4. MRI-guided in-bore biopsy. In the second part, the recommendations are discussed in detail and relevant background information is provided.Key Points:Citation FormatDie AG Uroradiologie und Urogenitaldiagnostik der Deutschen Röntgengesellschaft hat im Konsensusverfahren einheitliche Empfehlungen zur Vorbereitung und Durchführung der MRT der Prostata erarbeitet. In tabellarischer Form werden im ersten Teil detailliert Empfehlungen zu 1. Anamnestische Angaben vor einer MRT der Prostata, 2. Untersuchungsterminierung und -vorbereitung, 3. Untersuchungsprotokoll und 4. MRT gestützte In-bore-Biopsie gegeben. Im zweiten Teil werden die Empfehlungen ausführlich besprochen und die jeweiligen Hintergrundinformationen bereitgestellt.Kernaussagen:Zitierweise
Keywords: prostate; MRI; guideline